If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = -8 + b Solving 7 = -8 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 7 + -1b = -8 + b + -1b Combine like terms: b + -1b = 0 7 + -1b = -8 + 0 7 + -1b = -8 Add '-7' to each side of the equation. 7 + -7 + -1b = -8 + -7 Combine like terms: 7 + -7 = 0 0 + -1b = -8 + -7 -1b = -8 + -7 Combine like terms: -8 + -7 = -15 -1b = -15 Divide each side by '-1'. b = 15 Simplifying b = 15
| 3=7(x-2)+17 | | -18+5x=35-x | | 6x^3-11x^2-7x=0 | | -3(3x+1)-2=-4(x+1)+5x | | 5=m+16 | | X-5(-x-5)=-7 | | -6x+4(3x-7)=-19-3x | | 6x^2-9x+2=0 | | 5x^2+25=-7 | | 4(9-x)/(5)=x | | 9x^4-36x^2+32=0 | | -3a-(-8+3a)=-16 | | 13=1-x+x^2+9 | | 10x^4-17x^2+3=0 | | 0.4x+17=13 | | 6x-6=x+2 | | 2b^2-10b+9=0 | | x+3=x+2 | | 25x^3+70x^2+49x=0 | | 6x-6=x+3 | | 3x-1+13=6x | | 5x+2x-3=-10x+3x | | a(x-b)=c+ab | | 6a-8=18 | | -16+5f=-7(-6+8f)+3 | | x^2-x-25=0 | | 3(w-8)=36 | | 4m^4+32m^2+63=0 | | (1/2)x+=-5 | | 2(x-8)+x=3(x+6)+2 | | 4x^4-13x^2-12=0 | | 5x^4-9x^2-2=0 |